1998
DOI: 10.1159/000057385
|View full text |Cite
|
Sign up to set email alerts
|

Salt Intake and Renal Outcome in Patients with Progressive Renal Disease

Abstract: Experimental studies suggest that salt intake plays a critical role in the progressive glomerular filtration rate (GFR) loss of established renal disease; however, this issue has never been addressed in humans. To this aim, we have retrospectively analyzed the clinical data of patients with chronic renal failure (CRF), in whom a low-protein diet was prescribed, over a period of about 3 years. On the basis of the daily urinary sodium output, the patients were divided into two groups: a group of patients constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
82
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(87 citation statements)
references
References 19 publications
5
82
0
Order By: Relevance
“…In the present study, dietary salt intake was low (2.70 or 4.90 g/day). Cianciaruso et al 15 observed improvements in renal function and proteinuria with low sodium intake compared to high sodium intake in patients with progressive renal disease. Allen et al 16 reported suppression of hyperfiltration, renal enlargement and albuminuria by salt restriction in diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, dietary salt intake was low (2.70 or 4.90 g/day). Cianciaruso et al 15 observed improvements in renal function and proteinuria with low sodium intake compared to high sodium intake in patients with progressive renal disease. Allen et al 16 reported suppression of hyperfiltration, renal enlargement and albuminuria by salt restriction in diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…ROS activate mitogen-activated protein kinase in renal tubule cells (38), contribute to hypertrophic responses to Ang II (38) and to cellular injury (39), and increase fibrogenic matrix protein synthesis in mesangial cells (40). A high salt intake enhances oxidative stress in rat skeletal muscle arterioles and vessels (23) and increases BP, protein excretion, and renal fibrosis and worsens renal function in several models of chronic renal failure (7,38,(41)(42)(43) and accelerates the decline of renal function in patients with chronic renal failure (44). Conversely, salt restriction ameliorates renal disease progression in animal models (42) and is recommended for patients with chronic renal failure (45).…”
Section: Discussionmentioning
confidence: 99%
“…17 Consistently, observational studies in humans showed that increased dietary sodium intake increases proteinuria and accelerates renal disease progression. 18 However, no study thus far has evaluated the associations between salt intake, proteinuria, and renal disease progression in patients receiving RAS-inhibiting treatment. Hence, in this study, we evaluated the association of sodium intake with proteinuria and progression to ESRD in 500 patients with CKD retrieved from the Ramipril Efficacy in Nephropathy (REIN) [1][2][3] and REIN-2 19 trials who were receiving stable ramipril therapy.…”
mentioning
confidence: 99%